A thermo-degradable hydrogel with light-tunable degradation and drug release. (January 2017) - Hu, Jingjing; Chen, Yihua; Li, Yunqi; Zhou, Zhengjie; Cheng, Yiyun
Abstract: The development of thermo-degradable hydrogels is of great importance in drug delivery. However, it still remains a huge challenge to prepare thermo-degradable hydrogels with inherent degradation, reproducible, repeated and tunable dosing. Here, we reported a thermo-degradable hydrogel that is rapidly degraded above 44 °C by a facile chemistry. Besides thermo-degradability, the hydrogel also undergoes rapid photolysis with ultraviolet light. By embedding photothermal nanoparticles or upconversion nanoparticles into the gel, it can release the entrapped cargoes such as dyes, enzymes and anticancer drugs in an on-demand and dose-tunable fashion upon near-infrared light exposure. The smart hydrogel works well both in vitro and in vivo without involving sophisticated syntheses, and is well suited for clinical cancer therapy due to the high transparency and non-invasiveness features of near-infrared light.